Evolutionary Psychology of Eating Disorders: An Explorative Study in Patients With Anorexia Nervosa and Bulimia Nervosa - Nettersheim, Johanna; Gerlach, Gabriele; Herpertz, Stephan; Abed, Riadh; Figueredo, Aurelio J.; Brüne, Martin (Frontiers in Psychology, 2018)
Prior research on non-clinical samples has lent support to the sexual competition hypothesis for eating disorders (SCH) where the drive for thinness can be seen as an originally adaptive strategy for women to preserve a nubile female shape, which, when driven to an extreme, may cause eating disorders. Restrictive versus impulsive eating behavior may also be relevant for individual differences in allocation of resources to either mating effort or somatic growth, reflected in an evolutionary concept called “Life History Theory” (LHT). In this study, we aimed to test the SCH and predictions from LHT in female patients with clinically manifest eating disorders. Accordingly, 20 women diagnosed with anorexia nervosa (AN), 20 with bulimia nervosa (BN), and 29 age-matched controls completed a package of questionnaires comprising measures for behavioral features and attitudes related to eating behavior, intrasexual competition, life history strategy, executive functioning and mating effort. In line with predictions, we found that relatively faster life history strategies were associated with poorer executive functioning, lower perceived own mate value, greater intrasexual competition for mates but not for status, and, in part, with greater disordered eating behavior. Comparisons between AN and BN revealed that individuals with BN tended to pursue a “fast” life history strategy, whereas people with AN were more similar to controls in pursuing a “slow” life history strategy. Moreover, intrasexual competition for mates was significantly predicted by the severity of disordered eating behavior. Together, our findings lend partial support to the SCH for eating disorders. We discuss the implications and limitations of our study findings.